A Typological Analysis of South Korean Primary Teachers' Awareness of Primary Geography Education. Issue 2 (4th March 2018) - Lee, Dong-min
Abstract: This study illuminates primary teachers' awareness of geography education. Data were collected through interviews with twenty-one teachers and analyzed using Straussian-grounded theory. A total of 210 concepts were categorized into twenty-two categories. The participants were categorized into three types. Many participating teachers (type 1 and 2) were clearly aware of the core characteristics of geography, and some of them recognized themselves as primary geography specialists (type 1). However, a few teachers (type 3) seemed unaware of the value of geography. These results suggest the necessity of primary-teacher training to improve primary teachers' awareness of geography education.